Binder composition for negative electrode
Patent Information
- Application Number
- JP2023570306
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-14
- Filing Date
- 2022-05-12
- Publication Date
- 2025-04-18
AI Technical Summary
Existing polymer binders for lithium-ion battery negative electrodes face challenges in preventing hydrogen gas generation during the preparation of amorphous silicon-containing aqueous slurries, which poses safety concerns and limits the scalability of battery production.
The use of polymeric binders containing oxyalkylated functional groups, combined with other monomers, to form a composition that reduces hydrogen gas generation and enhances adhesion to current collectors, while maintaining low volatile organic compound content.
The composition effectively prevents hydrogen gas generation during large-scale anode production, ensuring improved safety and performance of lithium-ion batteries with enhanced adhesion and low resistivity.
Smart Images

Figure 2022241068000001
Abstract
Description
[Technical field]
[0001] The present invention relates to electrode-forming compositions useful for forming negative electrodes for use in electrochemical electrical energy storage devices and secondary batteries. [Background technology]
[0002] There is growing interest in lightweight, high-energy density secondary (rechargeable) battery technologies. Lithium-ion batteries (LIBs) are widely used as power sources for many devices, including household appliances, electric vehicles, and power tools. The growing popularity of zero-emission electric vehicles, especially long-range electric vehicles, has led to a demand for LIB technology with improved energy density and durability. To improve the energy density and overall performance of the battery, various components of the battery are being investigated. These components include the anode, cathode, electrolyte, and separator. The anode has the potential to increase the battery energy density, especially if improved binders are used in the anode.
[0003] In the manufacture of electrodes for such secondary batteries, water-based slurries are often preferred over solvent-based slurries due to environmental concerns. Typically, these electrodes are manufactured by dispersing the electrode-forming components in water, casting the slurry or paste as a thin film onto a current collector, and then drying the film to form the electrode. The function of the polymer binder is to bind the electrode-forming particulates onto the current collector. The electrode-forming particulates of the negative electrode (anode) of these secondary lithium-ion batteries typically include an active material (such as a carbonaceous material) that can reversibly absorb and release or host (intercalate) lithium ions to create reaction sites for the lithium ion electrochemical reaction (charging / discharging the battery), a conductive additive, a rheology modifier, and a polymer binder. The anode active material is a material that can donate or accept electrons during the charge / discharge cycle. The conductive additive is typically used to improve the electrical conductivity of the negative electrode (anode), which reduces the internal resistance of the battery and therefore improves the power output of the battery. The rheology modifier is typically present in the anode slurry formulation to adjust the slurry rheology of the electrode manufacturing casting process. Examples of rheology modifiers used in negative electrode formulations include carboxymethyl cellulose (CMC) and polyacrylic acid (PAA). The function of the polymer binder is to bind the anode components onto the current collector. Generally, styrene butadiene rubber (SBR) latex is the predominant anode binder.
[0004] It has been reported that amorphous silicon (Si) can be oxidized to generate H2 gas during the preparation of aqueous slurries for lithium-ion battery applications [K.Hays et al; J.Phys.Chem.C2018,122,18,9746-9754]. The use of Si in secondary batteries is important because it has the potential to increase the energy density of the negative electrode of Li-ion batteries. However, the generation of H2 poses safety concerns during large-scale battery manufacturing.
[0005] Ongoing industry trends of increasing battery energy density and advances in anode active materials are creating new challenges for traditional polymer binders. There remains a need for anode binders that provide secondary batteries with high energy density, no H2 evolution, and excellent service life. There is a need for binders that provide functional benefits to the anode beyond simply physically holding the active and conductive materials together and providing physical flexibility.
[0006] In "A conductive self healing polymeric binder using hydrogen bonding for Si anodes in lithium ion batteries" (Sci.Rep.2020,14966), ethylene oxide-containing monomers were copolymerized with other polymerizable monomers to prepare polymers for battery anode binder applications. The polymerization method for preparing the polymer was solution-phase polymerization using an organic solvent (e.g., dimethylformamide).
[0007] In "Ionically Conductive Self-Healing Binder for Low Cost Si Microparticles Anodes in Li-Ion Batteries" (Adv. Energy Mater. 2018, 1703138), polyethylene glycol containing reactive isocyanate functional groups was grafted onto polymer side chains to produce an ethylene oxide-containing polymer for battery anode binder applications.
[0008] In "Re-Engineering Poly(Acrylic Acid) Binder toward Optimized Electrochemical Performance for Silicon Lithium-Ion Batteries: Branching Architecture Leads to Balanced Properties of Polymeric Binders" (Adv. Funct. Mater. 2019, 1908558), an ethylene oxide-containing monomer [tetra(ethylene glycol) diacrylate] was copolymerized with acrylic acid to prepare a polymer for anode binder applications. An ethylene oxide-containing monomer with two reactive groups was used as a branching agent to produce a branched polymer.
[0009] In a paper titled "An Adhesive Vinyl-Acrylic Electrolyte and Electrode Binder for Lithium Batteries" by Binh Tran of the University of Central Florida, poly(ethylene glycol) methyl ether methacrylate containing ethylene oxide was copolymerized with other polymerizable monomers and a copolymer was prepared by solution polymerization in an organic solvent solution (such as ethyl acetate).
[0010] US Pat. No. 8,790,622 discloses formulations comprising one or more comb-structured amphiphilic copolymers rich in both hydrophobic and polyalkylene glycol monomers.
[0011] U.S. Pat. No. 9,834,698 discloses latex binders useful for preparing zero or low VOC coating compositions using polymerizable polyalkylene glycol monomers such as polyethylene glycol methacrylate in combination with either or both of an emulsifier or a polymerizable polyalkylene glycol monomer containing bulky hydrophobic groups substituted on the aromatic ring. Summary of the Invention [Problem to be solved by the invention]
[0012] New electrode-forming compositions for use on the current collector of an electrode in a non-aqueous secondary electrical energy storage device that have high energy density and excellent life performance of the secondary battery are desired. In the present invention, it has surprisingly been found that the disclosed polymers containing specific functional groups can be used as binders in electrode formulations to provide electrodes with low resistivity, good adhesion to the current collector, and low VOC content. In particular, the inventors have found that the disclosed electrode-forming compositions containing polymer binders with oxyalkylated functional groups are particularly useful as binders for active material layers on the anodes of secondary batteries.
[0013] Unexpectedly, and furthermore, the binder of the present invention can prevent the evolution of H2 gas during the preparation of the amorphous Si-containing aqueous slurry, which is advantageous for large-scale anode production where large amounts of hydrogen may be generated. [Means for solving the problem]
[0014] The present invention is directed to an electrode-forming composition for use on a current collector of an electrode in a non-aqueous electrical energy storage device, the electrode-forming composition comprising, consisting of, or consisting essentially of: a) at least one particulate electrode-forming material, b) a polymeric binder, and c) from 0 to 40% by weight of the polymeric binder of at least one crosslinker capable of reacting with the polymeric binder b).
[0015] The polymeric binder b) comprises, consists of or consists essentially of the following as polymerized monomers: i) 10 to 99 weight percent of the polymeric binder comprises, consists of, or consists essentially of at least one nonionic monoethylenically unsaturated monomer; ii) 0.5 to 42 weight percent of the polymeric binder comprises, consists of, or consists essentially of at least one oxyalkylated monomer having ethylenic unsaturation and terminated with hydrogen or an aryl or alkyl chain (which may be hydrophobic) and having the formula: [ka] During the ceremony: m, n, and p each represent the number of alkylene oxide units from 0 to 150, and m+n+p≧1; q represents an integer at least equal to 1, preferably 3≦(m+n+p)q≦150; R1, R2, and R3 represent either H, CH3, or CH2CH3, and R1, R2, and R3 may be the same or different; R4 represents a terminal group and is hydrogen, an alkyl chain having 1 to 60 carbon atoms, or an aryl chain having 5 to 60 carbon atoms; R represents a group comprising, consisting of or consisting essentially of at least one polymerizable olefinic unsaturation, preferably a group selected from at least one of the following: acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, in particular acrylic urethane, methacrylic urethane, α-α′-dimethyl-isopropenyl-benzyl urethane, allyl urethane, more preferably a group selected from at least one of the following: acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, even more preferably methacrylate groups and mixtures thereof; iii) 0-50% by weight of the polymeric binder comprises, consists of, or consists essentially of at least one ethylenically unsaturated ionic monomer, the at least one ethylenically unsaturated ionic monomer comprising, consisting of, or consisting essentially of at least one functional group selected from at least one of carboxylate, sulfonate, sulfate, phosphate, phosphonate, and / or acid, and / or salt, and / or anhydride forms thereof; iv) 0-10% by weight of the polymeric binder comprises, consists of, or consists essentially of at least one monomer, the at least one monomer comprising, consisting of, or consisting essentially of at least two ethylenic unsaturations; v) 0-10 wt.% of the polymeric binder comprises, consists of, or consists essentially of at least one ethylenically unsaturated monomer, the at least one ethylenically unsaturated monomer comprises, consists of, or consists essentially of at least one functional group capable of promoting a crosslinking reaction after polymerization, the at least one functional group may be selected from at least one of N-methylolamide, N-alkylolamide, hydroxyl, epoxy, silane, and keto; vi) 0-30% by weight of the polymeric binder comprises, consists of, or consists essentially of at least one ethylenically unsaturated monomer, the at least one ethylenically unsaturated monomer containing at least one functional group capable of promoting adhesion, which may be selected from silane, ureido, amine, hydroxyl, and combinations thereof.
[0016] Components b)i) through b)vi) add up to a total of 100% by weight of polymeric binder b).
[0017] The polymeric binder b) has a Tg of 55° C. or less and / or a minimum film-forming temperature of 25° C. or less.
[0018] The composition may also comprise, consist of, or consist essentially of the following optional ingredients: c) 0-40% by weight of the polymeric binder of at least one crosslinker capable of reacting with the polymeric binder b); d) 0-10% by weight of the polymer binder of one or more wetting agents; e) 0-10% by weight of the polymer binder of one or more dispersants; f) 0-10% by weight of the polymeric binder of one or more VOCs, and / or adhesion promoters, and / or coalescents; g) 0-200% by weight of the polymer binder of one or more rheology modifier additives; h) 0-10% by weight of the polymeric binder of one or more additives comprising, consisting of, or consisting essentially of cure inhibitors, surfactants, and mixtures thereof.
[0019] The electrode-forming composition disclosed herein may be in the form of a solution, dispersion, or paste, but is typically prepared as a slurry. The electrode can be formed by applying a layer of the electrode-forming slurry composition to a current collector. The conductive layer is then dried to form a layer of electrode material that is adhered to the current collector, i.e., an active material layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The binders of the present invention provide a matrix for particulate electrode-forming materials, which typically include active materials and conductive materials. The disclosed polymeric binders contain oxyalkylated monomers in combination with other functional monomers, which together can improve the performance of the polymeric binder in a negative electrode.
[0021] As used herein, the term "electrode" refers to a dried layer of an electrode-forming slurry composition cast onto a current collector. Typically, electrodes are manufactured by casting a slurry or paste of dispersed electrode-forming components and binder as a thin film and then drying the film to form the electrode. This dried film is referred to as the electrode.
[0022] As used herein, the term "electrode assembly" refers to a combination of a current collector and a dried electrode dried thereon. A slurry or paste of dispersed electrode-forming components and binder can be cast onto a current collector, such as copper or nickel foil, to form an electrode assembly. The electrode assembly can be further coated with a separator-forming slurry, such as alumina and binder dispersed in water. The separator slurry can be cast simultaneously with the electrode slurry in a one-step process using a dual or multi-die in a wet-on-wet process. Alternatively, the separator slurry can be cast onto the electrode after the electrode is dried, or a free-standing separator can be adhered to the electrode surface. Thus, the electrode assembly includes a current collector, a dried electrode film, and optionally a separator film on the top surface of the electrode.
[0023] As used herein, the term "slurry" refers to a free-flowing or free-flowing and / or pumpable suspension of finely divided solid materials and binders in water. Such finely divided solids may include, among others, polymeric binder particles, in addition to the solid particles that are typically electrochemically active and conductive materials necessary to form an electrode for a secondary battery. Additives such as dispersants used to improve the quality of the dispersion of the finely divided solid materials may also be dissolved in the water. The composition for use as an electrode may be deposited on a current collector by any method known in the art. Non-limiting examples of such application methods include spraying, rolling, draw bar application, bird bar application, gravure, slot coating, or other coil coating methods. The composition is dried, if necessary, by heating. The coating of the electrode-forming composition may be calendered, if necessary, before or after the drying step, to remove water and other volatile materials. The drying time, temperature, and vacuum used may be adjusted to achieve the desired drying.
[0024] A current collector is a material that collects and transports electrons during the charge / discharge cycle of a battery. There is no particular limitation on the current collector as long as it is electrically conductive. Any common anode or cathode current collector used in secondary batteries can be used in the present invention. Non-limiting examples of current collectors include copper, iron, aluminum, nickel, titanium, gold, etc. The current collector can be in the form of a mesh, foam, foil, rod, or another structural form that does not interfere with the function of the current collector. The material of the current collector varies depending on whether the electrode is a positive or negative electrode. The most common current collector for the negative electrode is a sheet or foil of copper (Cu) or nickel (Ni) metal. The electrode material needs to be applied and adhered to the surface of the current collector in the secondary battery, preferably a lithium-ion battery.
[0025] Particulate electrode forming material a) The particulate electrode-forming material a) comprises particulate active material and conductive particles held together (physically and / or chemically) by a polymeric binder b). Active material is a material capable of intercalating lithium ions, i.e., absorbing / releasing lithium ions. Such active materials are known in the art. Conductive particles are also known in the art and are materials capable of conducting electrons. Certain materials can perform both functions within the electrode.
[0026] Particulate electrode-forming materials include, but are not limited to, conductive carbon additives, carbon nanotubes (CNTs), artificial graphite, natural graphite, hard carbon, activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semicrystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, mixtures or composites of the aforementioned materials, and / or other materials known in the art or described herein as suitable for use as an anode in a lithium-ion battery. These particulates may include active materials, i.e., materials capable of inserting (accepting) lithium ions, and conductive materials. The electrode film of a lithium-ion capacitor and / or lithium-ion battery may include about 80 weight percent, preferably up to 94 weight percent, more preferably up to 98 weight percent of particulate anode-forming materials a) after drying. These electrode-forming materials a) are typically in the form of solid powders.
[0027] Conductive carbon materials such as carbon black and graphite powder are widely used in positive and negative electrodes to reduce the internal electrical resistance of electrochemical systems. Non-limiting examples of conductive carbon may include furnace black, acetylene black, CNT, fine graphite powder, evaporated graphite fiber, and Ketjen carbon black. The typical addition level of conductive carbon to the active material in the electrode-forming material a) is usually in the range of 0.1% to 20% by weight, more preferably in the range of 0.5% to 10% by weight of the total amount of particulate anode-forming material.
[0028] The amount of particulate anode-forming material a) (including both the active material and the conductive carbon) present in the electrode-forming composition may be from 50% to 99% by weight of the total dry weight of the composition, preferably from 80 to 98% by weight, and most preferably from 94 to 98% by weight of the total dry weight of the composition.
[0029] Polymer binder b) The electrode-forming slurry composition further comprises, consists of, or consists essentially of a polymeric binder b). The polymeric binder b) is present in the active material layer. One of the functions of the binder b) is to bind (chemically or physically) the particulate anode-forming material a) to form the electrode. The polymeric binder b) may be in the form of polymer particles. These polymeric particles may be provided in the form of an emulsion or latex.
[0030] The inventors have surprisingly found that the Tg of the disclosed polymer binder b) is preferably within a certain range. Tg is the temperature at which the physical properties of the polymer change from thermoplastic (e.g. flexible, soft, stretchable) to glassy physical properties that limit the flexibility and elongation of the polymer binder b). As a result, bending the electrode may lead to the formation of cracks (visible or microcracks) in the electrode, which reduces the performance of the electrode. To facilitate the handling of the electrode and to obtain good electrode performance, the Tg of the polymer binder b) is at or near room temperature, or preferably below room temperature, i.e., according to certain embodiments, preferably below 55°C, more preferably below 45°C, even more preferably below 35°C, and most preferably below 25°C, below 20°C, or below 10°C.
[0031] Without being bound by any theory, to obtain satisfactory electrode integrity using the electrode-forming composition disclosed herein (which may be in the form of an aqueous slurry), when the aqueous phase evaporates, the polymer binder b) latex particles coalesce into a continuous network, capable of holding (chemically or physically) the active material and conductive carbon in an interconnected electrode network. The minimum film-forming temperature (MFFT) of the polymer binder b) latex particles is the lowest temperature at which coalescence of the polymer particles occurs as the water evaporates to form a continuous film. The MFFT is defined as the lowest temperature at which the polymer binder b) particles coalesce to form a continuous film. The polymer binder b) advantageously has a MFFT at or below room temperature, i.e., according to certain embodiments, preferably below 55°C, more preferably below 50°C, less than 45°C, even more preferably below 35°C, most preferably below 25°C, or even below 20°C.
[0032] There is little or no need to add coalescents that contribute to the volatile organic content or volatile organic compounds (VOCs) of the electrode-forming slurry composition of the present invention. In one embodiment, the electrode-forming composition has a VOC content of 0 to less than 5 wt%, in another embodiment, 0 to less than 1 wt%, and in yet another embodiment, 0 to less than 0.1 wt%.
[0033] As discussed in more detail below, the polymeric binder b) comprises, consists of, or consists essentially of a number of specific monomers as polymerized monomers. The choice of polymerization method for the disclosed polymeric binder b) is not particularly limited. Any polymerization method can be used to synthesize the disclosed binder. Non-limiting examples of polymerization methods include solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, free radical polymerization, controlled polymerization, and ionic polymerization. In one preferred embodiment, the polymeric binder b) is prepared by free radical polymerization via emulsion polymerization.
[0034] The number average molecular weight of the disclosed binders is preferably 1000 g / mol or more, more preferably 5000 g / mol or more, and even more preferably 10,000 g / mol or more. As used herein, number average molecular weight is measured by gel permeation chromatography using polystyrene standards.
[0035] The polymer binder b) may have a volume average particle size of 30-500 nm or may be a mixture of different particle sizes of 30-500 nm. The particle size is preferably in the range of 30-400 nm, more preferably in the range of 40-350 nm, and even more preferably in the range of 50-300 nm. As used herein, the volume average particle size is determined by dynamic light scattering (DLS).
[0036] The amount of the polymer binder b) in the composition for the electrode-forming material a) is preferably 1 wt% or more, more preferably 2 wt% or more, and preferably 30 wt% or less, more preferably 20 wt% or less, based on the weight of the electrode-forming material a). When the amount of the polymer binder b) is within the above-mentioned range, it can provide good binding performance.
[0037] The monomers contained in the polymer binder b) are described in more detail below.
[0038] Nonionic monoethylenically unsaturated monomers i) The disclosed polymer binder b) may contain one or more nonionic monoethylenically unsaturated monomers i). The selection of the nonionic monoethylenically unsaturated monomers i) is not particularly limited. Non-limiting examples include acrylic acid esters and methacrylic acid esters, such as C1-C12 alkyl (meth)acrylates, styrene and its derivatives, vinyl acetate, vinyl versatate, (meth)acrylamide, (meth)acrylonitrile and its derivatives, diisobutylene, vinylpyrrolidone, vinylcaprolactam, and mixtures thereof. Nonionic monomers i) that provide corresponding low Tg polymers are preferred for the disclosed polymer binder b). For example, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate are preferred as monomers i). The weight percentage of the nonionic monoethylenically unsaturated monomer i) in the disclosed polymeric binder b) is preferably in the range of 10 to 99 wt.-%, more preferably in the range of 20 to 95 wt.-%, and particularly preferably in the range of 30 to 90 wt.-%, based on the weight of the polymeric binder b).
[0039] ii) oxyalkylated monomers having ethylenic unsaturation and terminating in hydrogen or an aryl or alkyl chain; The polymeric binder b) comprises, consists of, or consists essentially of various oxyalkylated monomers having ethylenic unsaturation and terminating with hydrogen or an aryl chain having from 5 to 60 carbon atoms or an alkyl chain having from 1 to 60 carbon atoms, which may be hydrophobic, where the oxyalkylated monomer ii) is represented by the formula: [ka] During the ceremony: m, n, and p each represent the number of alkylene oxide units from 0 to 150, and m+n+p≧1; q represents an integer at least equal to 1, preferably 3≦(m+n+p)q≦150; R1, R2, and R3 represent either H, CH3, or CH2CH3, and R1, R2, and R3 may be the same or different; R4 represents a terminal group and is hydrogen, an alkyl chain having 1 to 60 carbon atoms, or an aryl chain having 5 to 60 carbon atoms; R represents a group comprising, consisting of or consisting essentially of at least one polymerizable olefinic unsaturation, preferably a group selected from at least one of acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, in particular acrylic urethane, methacrylic urethane, α-α′-dimethyl-isopropenyl-benzyl urethane, allyl urethane, more preferably a group selected from at least one of acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, even more preferably methacrylate groups and mixtures thereof.
[0040] Non-limiting examples of these functional group-containing monomers ii) include polyalkylene glycol mono(meth)acrylates and their hydroxyl functionalized derivatives, polyalkylene glycol monoallyl ethers and their hydroxyl functionalized derivatives, polyalkylene glycol monovinyl ethers and their hydroxyl functionalized derivatives, and combinations thereof. These functional monomers ii) can be used alone or in combination.
[0041] The at least one oxyalkylated monomer ii) is present in the polymeric binder b) at 0.5% to 42% by weight of the total polymeric binder b) weight. The weight percentage of the oxyalkylated functional monomer ii) in the polymeric binder b) should preferably be in the range of 0.5 to 42% by weight, more preferably in the range of 1 to 30% by weight, and even more preferably in the range of 1.5 to 20% by weight, based on the weight of the polymeric binder b).
[0042] iii) ethylenically unsaturated ionic monomers containing at least one functional group selected from at least one of the following: carboxylate, sulfonate, sulfate, phosphate, phosphonate, and / or in the form of an acid and / or salt, and / or anhydride thereof; The polymeric binder b) may contain a monoethylenically unsaturated ionic monomer iii). The weight percentage of the monoethylenically unsaturated ionic monomer iii) in the disclosed polymeric binder b) is preferably in the range of 0-50 wt%, more preferably in the range of 5-40 wt%, and even more preferably in the range of 10-30 wt%, based on the weight of the polymeric binder b).
[0043] The selection of the monoethylenically unsaturated ionic monomer iii) is not particularly limited. It may be selected from monoethylenically unsaturated monomers containing at least one functional group selected from at least one of carboxylate, sulfonate, sulfate, phosphate, phosphonate, and / or its acid and / or salt, and / or anhydride forms. Non-limiting examples include (meth)acrylic acid, 2-carboxyethyl acrylate, 2-polycarboxyethyl acrylate, monoester of itaconic acid, maleic acid, fumaric acid, crotonic acid, itaconic acid, 2-acrylamido-2-methylpropanesulfonic acid, 4-styrenesulfonic acid, vinylsulfonic acid, 2-sulfoethyl methacrylate, phosphoric acid ester of polyalkylene glycol mono(meth)acrylate, polyalkylene glycol allyl ether phosphate, vinylphosphonic acid, acid form, and / or salt form, and / or anhydride form (if chemically possible) of 2-(methacryloyloxy)ethylphosphonic acid, and mixtures thereof.
[0044] The disclosed polymeric binder b) optionally containing ionic functional groups iii) and the hydrophilic functional oxyalkylated monomer ii) may increase in viscosity upon neutralization in aqueous solution. Thus, the disclosed polymeric binder b) may function as a self-thickening binder in the anode slurry. The self-thickening polymeric binder b) may be used with or without conventional rheology modifiers, such as carboxymethylcellulose (CMC), in the anode or cathode slurry formulation.
[0045] iv) Monomers containing at least two ethylenic unsaturations The polymeric binder b) may also comprise, consist of or consist essentially of at least one monomer iv) containing at least two ethylenic unsaturations. These monomers iv) containing at least two ethylenic unsaturations are capable of crosslinking the polymeric binder b) in situ during polymerization. Non-limiting examples of these monomers iv) are: allyl ethers obtained from polyols; preferably allyl ethers obtained from polyols and selected from at least one of pentaerythritol, sorbitol or sucrose; acrylic or methacrylic esters obtained from polyols, preferably acrylic or methacrylic esters obtained from polyols and selected from at least one of pentaerythritol, sorbitol or sucrose; divinylnaphthalene, trivinylbenzene, 1,2,4-trivinylcyclohexane, trivinyl ethers, tert-butyl ... Allyl pentaerythritol, diallyl pentaerythritol, diallyl sucrose, trimethylolpropane diallyl ether, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, diallyl itaconic acid, diallyl fumaric acid, diallyl maleate, butanediol dimethacrylate, ethylene di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, trimethylolpropane tri(meth)acrylate, methylene bis(meth)acrylamide, triallyl cyanurate, diallyl phthalate, divinylbenzene and mixtures thereof. More preferred monomer iv) may be selected from at least one of 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, ethylene di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, trimethylolpropane tri(meth)acrylate, diallyl phthalate, divinylbenzene and mixtures thereof. Even more preferred monomers iv) may be selected from at least one of 1,6-hexanediol di(meth)acrylate, allyl(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, diallyl phthalate, divinylbenzene, and mixtures thereof.
[0046] The crosslinking monomer iv) may be present in the polymer binder b) in an amount of 0 to 10% by weight, based on the weight of the polymer binder b). The crosslinking monomer iv) is preferably present in an amount of 0.01% to 7%, more preferably 0.1% to 5%, and most preferably 0.1% to 1%, based on the weight of the polymer binder b).
[0047] v) Ethylenically unsaturated monomers containing functional groups The disclosed polymer binder b) may further comprise, consist of, or consist essentially of one or more crosslinking monomers v) that contain functional groups that may allow for crosslinking reactions after polymerization (including optionally allowing the incorporation of the monomer into the polymer binder backbone). These ethylenically unsaturated functional monomers v) comprise, consist of, or consist essentially of at least one reactive group in addition to ethylenic unsaturation. When multiple reactive groups are present, the reactive groups may be the same or different. Suitable functional groups may be selected from at least one of N-methylolamide, N-alkylolamide, hydroxyl group, epoxy, silane, and keto group. The selection of the ethylenically unsaturated monomer v) is not limited. Non-limiting examples of ethylenically unsaturated monomers v) include at least one of N-methylol (meth)acrylamide, vinyl glycidyl ether, allyl glycidyl ether, glycidyl (meth)acrylate, diacetone acrylamide, acetaethoxyethyl methacrylate, (meth)acryloxyalkyltrialkoxysilane, vinyltrialkoxysilane, and mixtures thereof.
[0048] The weight percentage of monomer v) in polymeric binder b) is preferably in the range of 0 to 10 wt.-%, more preferably in the range of 0.05 to 7.5 wt.-%, even more preferably in the range of 0.1 to 5 wt.-%, based on the weight of polymeric binder b).
[0049] vi) Ethylenically unsaturated monomers containing functional groups The polymeric binder b) may further comprise, consist of, or consist essentially of one or more ethylenically unsaturated monomers vi) comprising a functional group. The functional group in monomer vi) may be selected from at least one of silane, ureido, amine, hydroxyl, and combinations thereof.
[0050] The choice of monomer vi) is not limited. Non-limiting examples of monomer vi) include (meth)acryloxyalkyltrialkoxysilanes, vinyltrialkoxysilanes, (meth)acrylic acid esters of substituted ureas, (meth)acrylamides of substituted ureas, allyl ethers of substituted ureas, aminoalkyl(meth)acrylates, hydroxyalkyl(meth)acrylates. These functional ethylenically unsaturated monomers vi) can be used alone or in combination to improve the performance of the polymer binder b) in the electrode.
[0051] According to one embodiment, monomer vi) may be selected from at least one of (meth)acryloxyalkyltrialkoxysilanes, vinyltrialkoxysilanes, (meth)acrylic acid esters of substituted ureas, (meth)acrylamides of substituted ureas, allyl ethers of substituted ureas, aminoalkyl (meth)acrylates, hydroxyalkyl (meth)acrylates, and mixtures thereof.
[0052] According to a preferred embodiment, monomer vi) may be selected from at least one of (meth)acryloxyalkyltrialkoxysilanes, vinyltrialkoxysilanes, aminoalkyl(meth)acrylates, hydroxyalkyl(meth)acrylates, and mixtures thereof.
[0053] The weight percentage of the ethylenically unsaturated monomer vi) in the polymer binder b) is preferably in the range of 0 to 30% by weight, preferably in the range of 0.01 to 10% by weight, more preferably in the range of 0.05 to 7.5% by weight, and even more preferably in the range of 0.1 to 5% by weight, based on the polymer binder b).
[0054] In particular, monomers vi) may contain silane or hydroxyl groups, as may some monomers v), so that, if monomers v) and vi) both contain one or more silane and hydroxyl groups, up to 40% by weight of monomers containing silane or hydroxyl groups may be present in the polymer binder b).
[0055] Crosslinker c) The disclosed compositions may also include an optional crosslinker c). The crosslinker c) may react with the functional groups of the disclosed polymeric binder b). For example, the post-crosslinkable functional groups in monomer v) may be crosslinked with or without an external agent. Some of the post-crosslinkable functional groups may react with themselves to crosslink. Some of the post-crosslinkable functional groups of v) may need to react with an external agent to form crosslinks. The crosslinker c) referred to herein is a separate component from the polymeric binder b) that can react with some of the post-crosslinkable functional groups in the polymeric binder b). The crosslinker c) can be added to the polymeric binder b) during the preparation of the binder. The crosslinker c) can also be added to the negative electrode slurry as a two-part binder composition during the manufacture of the electrode. The choice of the crosslinker c) is not particularly limited. Any crosslinker c) that contains two or more functional groups that can react with the polymeric binder b) or materials present in the negative electrode can be used as the crosslinker c). Non-limiting examples of reactive functional groups in crosslinker c) include, consist of, or consist essentially of silanes, epoxies, amines, alcohols, blocked isocyanates, aziridines, and carbodiimides. Suitable crosslinkers c) include, but are not limited to, at least one of the following: alkoxysilanes, alkoxysilane derivatives, dihydrazides, multifunctional hydrazides, diamines, multifunctional amines, diepoxys, multifunctional epoxies, diols, polyols, multifunctional blocked isocyanates, multifunctional aziridines, multifunctional carbodiimides, and mixtures thereof.
[0056] According to a preferred embodiment, the crosslinker c) may be selected from at least one of the following: γ-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, trimethoxypropylsilane, adipic acid dihydrazide, sebacic acid dihydrazide, valine dihydrazide, isophthalic acid dihydrazide, hexamethylenediamine, polyvinyl alcohol, bisphenol A diglycidyl ether, 1,4-butanediol diglycidyl ether, blocked polyisocyanates (e.g. Desmodur® BL3175S from Covestro). N), pentaerythritol tris(3-(1-aziridinyl)propionate), polycarbodiimide crosslinkers (e.g., CARBODILITE™ V-02, CARBODILITE™ V-02-L2, CARBODILITE™ SV-02, CARBODILITE™ V-10, CARBODILITE™ SW-12G, CARBODILITE™ E-02, CARBODILITE™ E-03A, CARBODILITE™ E-05, CARBODILITE™ E-07, manufactured by Nisshinbo), and combinations thereof.
[0057] According to a more preferred embodiment, the preferred crosslinking agent c) may be selected from at least one of the following: γ-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, adipic acid dihydrazide, hexamethylenediamine, polyvinyl alcohol, bisphenol A diglycidyl ether, 1,4-butanediol diglycidyl ether, blocked polyisocyanates (e.g. Desmodur® BL3175SN from Covestro), pentaerythritol tris(3-(1- aziridinyl)propionate), polycarbodiimide crosslinkers (e.g., CARBODILITE™ V-02, CARBODILITE™ V-02-L2, CARBODILITE™ SV-02, CARBODILITE™ V-10, CARBODILITE™ SW-12G, CARBODILITE™ E-02, CARBODILITE™ E-03A, CARBODILITE™ E-05, CARBODILITE™ E-07, manufactured by Nisshinbo), and combinations thereof.
[0058] According to an even more preferred embodiment, the crosslinker c) may be selected from γ-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, adipic dihydrazide, hexamethylenediamine, polyvinyl alcohol, polycarbodiimide crosslinkers (e.g. CARBODILITE™ V-02, CARBODILITE™ V-02-L2, CARBODILITE™ SV-02, CARBODILITE™ V-10, CARBODILITE™ SW-12G, CARBODILITE™ E-02, CARBODILITE™ E-03A, CARBODILITE™ E-05, CARBODILITE™ E-07, manufactured by Nisshinbo) and combinations thereof.
[0059] The weight percentage of the crosslinker c) relative to the polymer binder b) contained in the composition for use as an electrode is preferably in the range of 0 to 40 wt %, more preferably in the range of 0.01 to 20 wt %, and even more preferably in the range of 0.05 to 10 wt %, relative to the polymer binder b).
[0060] Optional ingredients / additives: The composition may also include the following optional ingredients: d) 0-10% by weight of the polymer binder of one or more wetting agents; e) 0-10% by weight of the polymer binder of one or more dispersants; f) 0-10% by weight of the polymeric binder of one or more volatile organic compounds (VOCs), and / or adhesion promoters, and / or coalescents; g) 0-200% by weight of the polymer binder of one or more rheology modifier additives; h) 0-10% by weight of the polymer binder of one or more additives selected from curing inhibitors, surfactants, and mixtures thereof.
[0061] Surfactants and / or anti-settling agents can be added to the binder slurry composition at 0-10 parts per 100 parts of water, preferably 0.1-10 parts, more preferably 0.5-5 parts. These anti-settling agents or surfactants are generally added to the binder dispersion after polymerization to improve storage stability and provide additional stabilization during slurry preparation. Some surfactant / anti-settling agent is also present in the composition remaining from the polymerization process. Useful anti-settling agents include, but are not limited to: ionic surfactants (such as alkyl sulfates, sulfonates, phosphates, etc.), phosphonates (such as sodium lauryl sulfate, ammonium lauryl sulfate, etc.), and partially fluorinated alkyl sulfates, carboxylates, phosphates, phosphonates (such as those sold under the CAPSTONE brand name by DuPont), and non-ionic surfactants (such as the TRITON® X series (by Dow) and the PLURONIC® series (by BASF)). In one embodiment, only anionic surfactants are used. It is preferred that there be no residual surfactant in the composition from the polymerization process, or fluorinated surfactant added after polymerization in forming or concentrating the aqueous dispersion.
[0062] Wetting agents can be incorporated into the composition at 0-5 parts per 100 parts water, preferably 0-3 parts. Surfactants function as wetting agents, but wetting agents can also include non-surfactants. In some embodiments, the wetting agent can be an organic solvent. The presence of any wetting agent can allow the powdered inorganic material to be uniformly dispersed in the aqueous dispersion of vinylidene fluoride polymer. Useful wetting agents include, but are not limited to: ionic and non-ionic surfactants (such as the TRITON® series (Dow) and the PLURONIC® series (BASF)), organic liquids compatible with aqueous dispersions (including, but not limited to, NMP, DMSO, and acetone).
[0063] Thickeners and rheology modifiers can be present in the fluoropolymer separator composition in an amount of 0-10 parts per 100 parts water, preferably 0-5 parts. The addition of water-soluble thickeners or rheology modifiers to the above dispersions can prevent or retard settling of inorganic powder materials while providing a suitable slurry viscosity for the coating process. Useful thickeners include, but are not limited to: ACRYSOL series (Dow Chemical), Rheotech series (Coatex), Viscoatex series (Coatex), partially neutralized poly(acrylic acid) or poly(methacrylic acid) (such as CARBOPOL from Lubrizol or Viscodis 100N from Coatex), and carboxylated alkyl celluloses such as carboxylated methyl cellulose (CMC). Adjusting the pH of the formulation can improve the effectiveness of some thickeners. In addition to organic rheology modifiers, inorganic rheology modifiers can also be used alone or in combination. Useful inorganic rheology modifiers include, but are not limited to, inorganic rheology modifiers (including, but not limited to, natural clays such as montmorillonite and bentonite), artificial clays such as laponite, silica, and other clays such as talc.
[0064] The optional temporary adhesion promoter serves to create the necessary interconnectivity of the coating formed from the composition of the present invention. As used herein, "temporary adhesion promoter" refers to an agent that enhances the interconnectivity of the composition after coating. The temporary adhesion promoter can then be removed from the substrate on which it is formed, typically by evaporation (in the case of chemicals) or dissipation (in the case of the addition of energy).
[0065] The temporary adhesion promoter may be a chemical, an energy source combined with pressure, or a combination thereof, used in an amount effective to cause interconnection of the components of the aqueous composition during the formation of the electrode. In the case of chemical temporary adhesion promoters, the composition comprises 0-150 parts, preferably 0-100 parts, more preferably 0-30 parts of one or more temporary adhesion promoters per 100 parts of water. Preferably, this is a water-soluble or water-miscible organic liquid. The organic liquid acts as a plasticizer or coalescer for the acrylic particles, giving them tackiness and allowing them to function as individual adhesion points during the drying step. The binder particles soften, flow, and are able to adhere to the powder material during the drying stage, resulting in an electrode with high irreversible connectivity. In one embodiment, useful organic solvents or coalescers include, but are not limited to, those in the table below.
[0066] JPEG2024519351000003.jpg48109
[0067] In the case of energy as a temporary adhesion promoter, useful energy sources include, but are not limited to, heat, IR radiation, and radio frequency (RF). In the case of heat alone, the temperature during processing of the electrode should be about 20-50°C above the glass transition point of the acrylic binder. When using energy alone as a temporary adhesion promoter, it is preferable to combine heat with pressure, such as in a calendaring process, to obtain good interconnectivity, high adhesion to the current collector, and high cohesion within the electrode.
[0068] Usage: The electrode composition of the present invention is suitable for use on a current collector in an electrical energy storage device containing a non-aqueous electrolyte, such as a secondary battery device, such as a device that includes an anode, a cathode, a separator between the anode and cathode, and an electrolyte.
[0069] Disclosed are electrodes, such as anodes, comprising the compositions in dry form for use as an electrode on a substrate (i.e., current collector) in an electrical energy storage device. Such electrodes are preferably used as anodes, and thus the compositions disclosed herein for use as electrodes are most preferably applied to a conductive substrate current collector made from copper.
[0070] Also provided is an electrical energy storage device selected from at least one of a non-aqueous battery, a capacitor, and a membrane electrode assembly, which incorporates an electrode comprising a conductive substrate, in dry form, coated on at least one surface with a composition for use as an electrode disclosed herein.
[0071] kit The composition for use as an electrode on a current collector in an electrical energy storage device containing a non-aqueous electrolyte may be provided in the form of a kit. Thus, at least one crosslinker c) may be combined with a polymeric binder b) to form a first component of the kit; and at least one particulate electrode-forming material a) may be a second component of the kit.
[0072] Another embodiment of the kit is also provided, in which the at least one particulate electrode-forming material a) can be a first component of the kit; the polymer binder b) can be a second component of the kit; and the at least one cross-linking agent c) can be a third component of the kit. EXAMPLES
[0073] The electrodes were calendered at room temperature at very high pressure to reach the desired porosity. The porosity of the electrode was back-calculated from its predicted (weight contribution of each component) and apparent density, which was obtained by measuring the weight and volume of the electrode using a micrometer and a 5-decimal balance.
[0074] Volume average particle size was measured by dynamic light scattering using a Nanotrac UPA150 from Microtrac.
[0075] Example 1: Binder manufacturing An initial charge of 800.00 g of deionized water and 0.78 g of Rhodacal® A-246MBA was added to a 1 gallon reactor. The initial charge consisted of 211.35 g of 2-ethylhexyl acrylate, 230.19 g of styrene, 20.03 g of methyl methacrylate, 11.11 g of sodium 4-vinylbenzenesulfonate, 5.00 g of Silane A174, 25.00 g of PEGMA (M nA monomer pre-emulsion was prepared by weighing 1.22 g of ammonium persulfate into a first glass beaker and mixing with 11.92 g of Rhodacal® A-246MBA and 227.24 g of deionized water. An initial initiator was prepared by weighing 1.22 g of ammonium persulfate into a second glass beaker and dissolving in 15.00 g of deionized water. A delayed initiator was prepared by dissolving 0.55 g of ammonium persulfate in 32.00 g of water in a third beaker. The reactor contents were heated to a temperature of 83±2° C. 37.09 g of the monomer pre-emulsion and the initial initiator were initially introduced into the reactor. After the peak of the reaction exotherm, the remaining monomer pre-emulsion and the delayed initiator were fed into the reactor while maintaining the reactor temperature at 90±2° C. The delayed initiator solution was fed into the reactor over 260 minutes. The monomer pre-emulsion was fed to the reactor in four stages. 176.18 g of the monomer pre-emulsion was fed to the reactor over 45 minutes, followed by a 15 minute pause in the feed. The remaining monomer pre-emulsion was then fed to the reactor following the same feed profile over three stages. After completion of the delayed initiator feed over 260 minutes, the contents in the reactor were conditioned for 30 minutes, after which the medium was cooled to 70° C. During the 30 minutes of conditioned, a post-oxidizer solution was prepared in a glass beaker, containing 2.88 g of 70% t-butyl hydroperoxide and 23.30 g of deionized water. A post-reducer solution was also prepared in a glass beaker, containing 2.00 g of Bruggolite® FF6M and 45.00 g of deionized water. Then, after the 30 minutes of conditioned, the post-oxidizer and post-reducer solutions were fed to the reactor over 45 minutes. The medium was allowed to cool and filtered.
[0076] Example 2: Binder manufacturing The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0077] Example 3: Binder manufacturing The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0078] Example 4: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0079] Example 5: Binder production The binders were prepared in a manner similar to that of Example 1, except that the monomer selection and ratios were different. The weight percent of each monomer relative to the total monomers used is shown in Table 1.
[0080] Example 6: Binder production An initial charge of 533.67 g of deionized water, 0.40 g of ammonium hydroxide, and 1.40 g of Rhodacal® A-246MBA was added to a 1 gallon reactor. The initial charge consisted of 458.32 g of 2-ethylhexyl acrylate, 346.56 g of styrene, 36.14 g of methyl methacrylate, 29.00 g of Sipomer® PAM600, 31.57 g of AAEM, 16.24 g of PEGMA (M nA monomer pre-emulsion was prepared by weighing 2.20 g of ammonium persulfate into a first glass beaker and mixing with 5.40 g of Rhodacal® A-246MBA and 365.00 g of deionized water. An initial initiator was prepared by weighing 2.20 g of ammonium persulfate into a second glass beaker and dissolving in 15.00 g of deionized water. A delayed initiator was prepared by dissolving 1 g of ammonium persulfate in 32.00 g of water in a third beaker. A third stream of base feed was prepared by dissolving 4.00 g of ammonium hydroxide in 29.00 g of water in a fourth beaker. The reactor contents were heated to a temperature of 83±2° C. 64.41 g of the monomer pre-emulsion and the initial initiator were initially introduced into the reactor. After the peak of the reaction exotherm, the remaining monomer pre-emulsion, the third stream base feed and the delayed initiator were fed to the reactor while maintaining the reactor temperature at 90±2° C. The delayed initiator solution and the third stream base were fed to the reactor over 260 minutes. The monomer pre-emulsion was fed to the reactor in four stages. 305.96 g of monomer pre-emulsion was fed to the reactor over 45 minutes, followed by a 15 minute pause in the feed. The remaining monomer pre-emulsion was then fed to the reactor following the same feed profile over three stages. After completion of the delayed initiator feed over 260 minutes, the contents in the reactor were conditioned for 30 minutes, after which the medium was cooled to 70° C. During the 30 minute conditioned period, a post-oxidizer solution was prepared in a glass beaker containing 3.90 g of 70% t-butyl hydroperoxide and 23.30 g of deionized water. A post-reducer solution was also prepared in a glass beaker containing 2.70 g of Bruggolite® FF6M and 45.00 g of deionized water. Then, after 30 minutes of preparation, the post-oxidizer and post-reducer solutions were fed into the reactor over 75 minutes. The medium was allowed to cool and filtered.
[0081] Comparative Example 1: Preparation of binder An initial charge consisting of 533.67 g of deionized water and 1.40 g of Rhodacal® A-246 MBA was introduced into a one gallon reactor. 434.77 g of 2-ethylhexyl acrylate, 434.33 g of styrene, 36.14 g of methyl methacrylate were weighed into a first glass beaker and mixed with 21.50 g of Rhodacal® A-246 MBA and 410.00 g of deionized water to prepare a monomer pre-emulsion. 2.20 g of ammonium persulfate was weighed into a second glass beaker and dissolved in 15.00 g of deionized water to prepare an initial initiator. 1.00 g of ammonium persulfate was dissolved in 32.00 g of water in a third beaker to prepare a delayed initiator. The reactor contents were heated to a temperature of 83±2°C. 66.84 g of monomer pre-emulsion and initial initiator were initially introduced into the reactor. After the peak of the reaction exotherm, the remaining monomer pre-emulsion, the third stream base feed and the delayed initiator were fed into the reactor while maintaining the reactor temperature at 90±2° C. The delayed initiator solution and the third stream base were fed into the reactor over 260 minutes. The monomer pre-emulsion was fed into the reactor over four stages. 317.48 g of monomer pre-emulsion was fed into the reactor over 45 minutes, after which the feed was paused for 15 minutes. The remaining monomer pre-emulsion was then fed into the reactor following the same feed profile over three stages. After completion of the delayed initiator feed over 260 minutes, the contents in the reactor were conditioned for 30 minutes, after which the medium was cooled to 70° C. During the 30 minutes of conditioned, a post-oxidizer solution was prepared in a glass beaker containing 2.60 g of 70% t-butyl hydroperoxide and 23.30 g of deionized water. A post-reducer solution was also prepared in a glass beaker containing 1.80 g of Bruggolite® FF6M and 45.00 g of deionized water. Then, after 30 minutes of preparation, the post-oxidizer and post-reducer solutions were fed into the reactor over 75 minutes. The medium was allowed to cool and filtered.
[0082] Preparation of anode slurry Seven 6.5 mm zirconia balls were placed in a 125 mL polyethylene container of a Thinky ARE-310. 0.25 g carbon black (Super P-Li from Timcal) + 4.5 g of carboxymethyl cellulose (CMC) solution at 1.5% solids in water (BVH9 from Ashland Chemicals) and 9.1 g graphite (GHDR15-4 from Imerys) + 2.5 grams of silicon (amorphous silicon from NanoAmor) were added and mixed at 2000 rpm for 2 minutes. Then, 1.0 g of CMC solution was added consecutively and mixed at 2000 rpm for 2 minutes, followed by another CMC solution and mixing to reach a total CMC solution addition of 10.0 g. Then, 2.5 g of the above example at 20 wt% solids was added and mixed twice at 2000 rpm for 2 minutes.
[0083] Electrode manufacturing and testing: The slurry prepared above was cast onto copper foil with a wet thickness of about 110 μm and placed in a convection oven at 120 °C for 30 min. The electrode was then calendered to reach a porosity of about 30% by volume. Adhesion measurements were performed on an Instron using 1-inch wide electrode specimens according to ASTM-D903 (2017) with a 180 degree peel at a crosshead speed of 50 mm / min.
[0084] [Table 1]
[0085] Abbreviation: 2EHA = 2-ethylhexyl acrylate i) A174 = 3-(triethoxysilyl)propyl methacrylate v) / vi) AAEM = Acetoacetoxyethyl methacrylate v) CMC = Carboxymethylcellulose DAAM = diacetone acrylamide v) DVB = Divinylbenzene (iv) MMA = methyl methacrylate PAA = Polyacrylic acid PAM4000 = Sipomer® PAM4000 (phosphate ester of ethyl methacrylate) iii) PAM600 = Sipomer® PAM600 (phosphate ester of polypropylene glycol monomethacrylate) iii) PEGMA = Poly(ethylene glycol) methyl ether methacrylate ii) SBR = Styrene butadiene rubber SSS = Sodium 4-vinylbenzenesulfonate iii) Sty = styrene
[0086] All the examples in Table 1 were evaluated in the negative electrode formulation to compare their performance in slurry preparation and electrode adhesion. In the slurry preparation step, stable slurries were prepared using all of the inventive examples 1-6. However, comparative example 1 failed to prepare a slurry. Agglomerated solids were observed when the slurry was prepared in comparative example 1. A direct comparison between inventive example 5 and comparative example 1 in the slurry preparation demonstrates the improvement provided by the PEGMA monomer (monomer ii).
[0087] Table 1 lists the peel adhesion of the electrodes prepared in Examples 1-6 of the present invention. Peel adhesion is a measure of the binding ability of the binder in the electrode. High peel adhesion is favorable for electrode processing and battery cycling. Generally, 10 N / m or more is preferred for electrode processing. The peel adhesion of all the present invention examples is greater than 10 N / m. The peel adhesion of Comparative Example 1 is not available due to the instability of the slurry. Furthermore, the present invention examples 1, 3 and 6, which contain additional functional monomers, show improved peel adhesion compared to the present invention example 5. These functional monomers iii), v), and vi) further improve the peel adhesion of the electrode, which is beneficial for electrode processing and battery cycling.
[0088] Although the invention has been illustrated and described herein with reference to specific embodiments, it is not intended that the invention be limited to the details shown, but rather various changes in the details can be made within the scope of the claims and equivalents without departing from the invention.
Claims
1. 1. A composition for use as an electrode on a current collector in an energy storage device containing a non-aqueous electrolyte, the composition comprising: a) at least one particulate electrode-forming material; b) a polymeric binder comprising as polymerized monomers: i) 10 to 99 weight percent of the polymeric binder of at least one nonionic monoethylenically unsaturated monomer; ii) 0.5 to 42 percent by weight of the polymeric binder of at least one oxyalkylated monomer having ethylenic unsaturation and terminated with hydrogen or an aryl or alkyl chain and having the formula: 【Chemistry 1】 During the ceremony: m, n, and p represent the number of alkylene oxide units from 0 to 150, and m+n+p≧1; q represents an integer at least equal to 1, preferably 3≦(m+n+p)q≦150; R 1 , R 2 , and R 3 is H, CH 3 or CH 2 CH 3 R represents any one of the following: 1 , R 2 , and R 3 may be the same or different, R 4 represents an end group, which is hydrogen, an alkyl chain having 1 to 60 carbon atoms, or an aryl chain having 5 to 60 carbon atoms; R represents a group comprising at least one polymerizable olefinically unsaturated group, preferably a group selected from at least one of the following: acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl, isoprenyl, unsaturated urethane groups, in particular acrylic urethane, methacrylic urethane, α-α′-dimethyl-isopropenyl-benzyl urethane, allyl urethane, more preferably a group selected from at least one of the following: acrylate, methacrylate, acrylic urethane, methacrylic urethane, vinyl, allyl, methallyl and isoprenyl, esters of maleic acid, esters of itaconic acid, esters of crotonic acid, even more preferably methacrylate groups and mixtures thereof; iii) 0-50% by weight of the polymeric binder of at least one ethylenically unsaturated ionic monomer containing at least one functional group selected from carboxylate, sulfonate, sulfate, phosphate, phosphonate, and / or the acid, and / or salt, and / or anhydride forms thereof, and combinations thereof; iv) 0 to 10% by weight of the polymeric binder of at least one monomer containing at least two ethylenic unsaturations; v) 0-10% by weight of the polymeric binder of at least one ethylenically unsaturated monomer containing at least one functional group selected from N-methylolamide, N-alkylolamide, hydroxyl, epoxy, silane, keto, and combinations thereof; vi) 0 to 30% by weight of the polymeric binder of at least one ethylenically unsaturated monomer containing at least one functional group selected from silane, ureido, amine, hydroxyl, and combinations thereof; wherein the polymer binder b) has a Tg of 55° C. or less and / or a minimum film-forming temperature of 25° C. or less; The sum of components b)i) through b)vi) represents up to 100% by weight of the polymeric binder b); c) 0-40% by weight of the polymeric binder of at least one crosslinker capable of reacting with the polymeric binder b); d) 0-10% by weight of the polymeric binder of one or more humectants; e) 0-10% by weight of the polymer binder of one or more dispersants; f) 0-10% by weight of the polymeric binder of one or more volatile organic compounds (VOCs), and / or adhesion promoters, and / or coalescents; g) 0-200% by weight of the polymeric binder of one or more rheology modifier additives; and h) 0-10% by weight of the polymeric binder of one or more additives including at least one of an inhibitor, a surfactant, and mixtures thereof.
2. 2. The composition of claim 1, wherein monomer ii) comprises at least one of polyalkylene glycol mono(meth)acrylates and hydroxyl group functionalized derivatives thereof, polyalkylene glycol monoallyl ethers and hydroxyl group functionalized derivatives thereof, polyalkylene glycol monovinyl ethers and hydroxyl group functionalized derivatives thereof, and combinations thereof.
3. 10. The composition of claim 1, wherein the at least one crosslinker c) comprises at least one of an epoxy, an amine, an alcohol, a blocked isocyanate, a carbodiimide, a polyfunctional aziridine, a silane, and mixtures thereof.
4. The composition of claim 1, wherein the polymer binder b) has a volume average particle size of 30 to 500 nm or is a mixture of different particle sizes of 30 to 500 nm.
5. 2. The composition according to claim 1, wherein the polymeric binder b) has a number average molecular weight of 1000 g / mol or more, more preferably 5000 g / mol or more, particularly preferably 10,000 g / mol or more.
6. The composition of claim 1, wherein monomer i) comprises at least one of the following: C1-C12 alkyl (meth)acrylates, styrene and its derivatives, vinyl acetate, vinyl versatate, (meth)acrylamide, (meth)acrylonitrile and its derivatives, diisobutylene, vinylpyrrolidone, vinyl caprolactam, and mixtures thereof.
7. The composition of claim 1, wherein monomer iii) comprises at least one of the following: (meth)acrylic acid, 2-carboxyethyl acrylate, 2-polycarboxyethyl acrylate, itaconic acid monoester, maleic acid, fumaric acid, crotonic acid, itaconic acid, 2-acrylamido-2-methylpropanesulfonic acid, 4-styrenesulfonic acid, vinylsulfonic acid, 2-sulfoethyl methacrylate, phosphate esters of polyalkylene glycol mono(meth)acrylates, polyalkylene glycol allyl ether phosphates, vinylphosphonic acid, 2-(methacryloyloxy)ethylphosphonic acid, and / or the acid and / or salt and / or anhydride forms thereof, and mixtures thereof.
8. The composition of claim 1, wherein monomer iv) comprises at least one of the following: allyl ethers derived from polyols; acrylic or methacrylic esters derived from polyols; divinyl naphthalene, trivinyl benzene, 1,2,4-trivinyl cyclohexane, triallyl pentaerythritol, diallyl pentaerythritol, diallyl sucrose, trimethylolpropane diallyl ether, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, diaryl itaconate, diallyl fumarate, diallyl maleate, butanediol dimethacrylate, ethylene di(meth)acrylate, poly(ethylene glycol) di(meth)acrylate, trimethylolpropane tri(meth)acrylate, methylene bis(meth)acrylamide, triallyl cyanurate, diallyl phthalate, divinyl benzene, and mixtures thereof.
9. The composition of claim 1, wherein monomer v) comprises at least one of the following: N-alkylol (meth)acrylamide, vinyl glycidyl ether, allyl glycidyl ether, glycidyl (meth)acrylate, diacetone acrylamide, acetoacetoxyethyl methacrylate, (meth)acryloxyalkyltrialkoxysilane, vinyltrialkoxysilane, and mixtures thereof.
10. 10. The composition of claim 1 , wherein monomer vi) comprises at least one of the following: (meth)acryloxyalkyltrialkoxysilanes, vinyltrialkoxysilanes, (meth)acrylic acid esters of substituted ureas, (meth)acrylamides of substituted ureas, allyl ethers of substituted ureas, aminoalkyl (meth)acrylates, hydroxyalkyl (meth)acrylates, and mixtures thereof.
11. a) the at least one particulate electrode-forming material comprises one or more materials selected from the following: furnace black, acetylene black, ketjen carbon black, carbon nanotubes (CNTs), artificial graphite, natural graphite, hard carbon, soft activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, and mixtures or composites thereof.
12. An electrode comprising a conductive substrate coated on at least one side with the composition according to any one of claims 1 to 11.
13. 13. A device comprising the electrode of claim 12, the device being selected from the group consisting of a non-aqueous battery, a capacitor, and a membrane electrode assembly.
14. A kit comprising the composition according to any one of claims 1 to 11, at least one crosslinker c) and a polymeric binder b) in combination form a first component of said kit; a) at least one particulate electrode-forming material comprising a second component of said kit.
15. A kit comprising the composition according to any one of claims 1 to 11, a) at least one particulate electrode-forming material constitutes a first component of the kit; b) a polymeric binder constitutes a second component of the kit; and c) at least one cross-linking agent constitutes a third component of the kit.